Healthy Living: Are You At Risk for Diabetes? FCS8573/FY076, rev. 11/2012 - Wittkowsky, Paulina; Bobroff, Linda B. (EDIS, 2011)
Revised! FCS8573 is a 1-page fact sheet by Paulina Wittkowsky and Linda B. Bobroff. Published by the UF Department of Family, Youth, and Community Sciences, January 2011, with a minor revision in November 2012.